The toxicity of petroleum pollutants on marine zooplankton: Multiscale effects from individuals to populations - Tianrui Liu; Xiahui Liu; Wangguangming Yu; Jingfeng Bai; Wei Shen; Xuan Wu (Marine Pollution Bulletin, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

Constructing electronic-ionic bicontinuous networks for high-fidelity bioelectrical monitoring with 24-hour stable interfaces - Guangyuan Xu; Chuantian Ren; Weiguang Wang; Yufeng Wu; Yiqian Zhou; Ming Lei; Jingfeng Zhang; Kai Huang; Hui Wu (Chemical Engineering Journal, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Al-Content-Tuned Ni-Based amorphous Silica-Alumina catalysts for efficient hydrodeoxygenation of lignin phenols under mild conditions - Jingfeng Wu; Jie Pan; Shenliang Hou; Xiaorui Du; Shurong Wang (Fuel, 2026)

Theory, application and prospect of full-life-cycle operation and maintenance technique system in coal underground water reservoir - Jiahui Song; Hanpeng Wang; Wei Wang; Bing Zhang; Wenqi Zheng; Yunhao Wu; Jingfeng Li; Jie Fang; Baoyang Wu; Zhengdai Li (Tunnelling and Underground Space Technology, 2026)

Synthesis of BMP wrist epitope-derived peptide functionalized bioink for 3D bioprinting of tissue-engineered bone constructs - Fei Huang; Guozhen Wei; Ying Zhang; Bing Wu; Yaoqing Chen; Yaoyu Qiu; Jingfeng Li; Gui Wu (Chemical Engineering Journal, 2026)

Bio-electrochemical regulation of sulfur transformations for boosted sulfur-based denitrification and integrated sulfate abatement: Performance and mechanisms - Jingfeng Ding; Gaoming Wu; Dazhi Bai; Bin Yang; Yang Hou; Lecheng Lei; Zhongjian Li (Journal of Environmental Chemical Engineering, 2026)

Transformation mechanisms of dissolved organic matter in a full-scale initial rainwater treatment plant: An empirical study based on ultra-high-resolution mass spectrometry and microbial community analysis - Xiaowen Chen; Qiankun Liu; Shengjie Zhao; Jingwei Feng; Jingfeng Wang; Hao Yin; Daoyun Wu (Journal of Environmental Chemical Engineering, 2026)

Transcriptomics and single cell sequencing revealed the important role of PPAR signaling pathway in zebrafish liver fibrosis induced by thioacetamide - Yilong Cui; Mula Na; Xinxin Zhang; Jie Wang; Lei Song; Qianxun Wang; Chi Feng; Xiaodong Hu; Jianhua Yu; Guiying Kang; Wu Dong; Jingfeng Yang (Environmental Pollution, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Editor's note to “The Grain-for-Green project offsets warming-induced soil organic carbon loss and increases soil carbon stock in Chinese Loess Plateau” [Sci. Total Environ. 837 (2022), 155469] - Huiwen Li; Yiping Wu; Shuguang Liu; Wenzhi Zhao; Jingfeng Xiao; Leigh A. Winowiecki; Xiaowei Yin; Fan Wang; Bellie Sivakumar; Yue Cao; Pengcheng Sun (Science of The Total Environment, 2026)

Editor's Note to “Remote sensing and modeling fusion for investigating the ecosystem water‑carbon coupling processes” [Sci. Total Environ. 697 (2019), 134064] - Pengcheng Sun; Yiping Wu; Jingfeng Xiao; Jinyu Hui; Jingyi Hu; Linjing Qiu (Science of The Total Environment, 2026)

Pulmonary sclerosing pneumocytoma with lymph node metastasis and high 18FDG uptake in PET/CT: a rare case report and literature review - Jingfeng Xu; Yilei Zhao; Qiuli Wu; Feng Chen (Journal of Zhejiang University-SCIENCE B, 2026)

Causal effects of immune cell populations on biological aging: a Mendelian randomization study - Jingfeng Fu; Wei Wu; Shangren Shen (Biogerontology, 2026)

Environmental DNA reveals shift in phytoplankton community driven by sewage-derived eutrophication in coastal waters - Jie Su; Xuexin Wu; Tingting Shi; Shanshan Dong; Daoyang Shi; Hanjun Chen; Hongxia Ming; Jingfeng Fan (Marine Environmental Research, 2026)

Disentangling the climate–VPD–GPP Nexus: Global patterns and underlying drivers - Shanshan Chen; Jingfeng Xiao; Xing Li; Minchao Wu; Jie Yang (Global and Planetary Change, 2026)

Electrochemically assisted activation of peroxymonosulfate by Cu-Co bimetallic carbon nitride for enhanced deoxynivalenol degradation - Bingjie Wang; Xi Zhang; Zhixia Wu; Chenyu Li; Jingfeng Wang; Xu Han (Journal of Environmental Chemical Engineering, 2025)

Stress-Permeability Modeling of Sandstone Using Wave Velocity-Based Porosity Evolution - Zhengdai Li; Jianping Zuo; Jingfeng Li; Yunjiang Sun; Meilu Yu; Yong Zhang; Baoyang Wu (Geotechnical and Geological Engineering, 2025)

A strategy for effective flocculation and sedimentation of coal gasification fine slag using a composite reagent system of CTAC/PDADMAC/NPAM - Jiawei Wu; Jingfeng He; Xinyao Wang; Hailong Tang; Bin Yang; Lingtao Zhu (Journal of Water Process Engineering, 2025)

Net ecosystem exchange of CO2 and its driving mechanisms in an island forest nature reserve in southern China - Liangxu Wu; Shuya Xie; Xianglan Li; Pengpeng Tian; Zhe Xu; Yuting Huang; Jingfeng Xiao; Xintong Chen; Minghai Xu; Wei Chen; Houcai Cai (CATENA, 2025)

Hypertension Induces Cognitive Impairment and Alterations of Acetylcholine Receptor mRNA Expression in the Hippocampus and Cortex of Mice - Jingfeng Liu; Jianting Hou; Jianlin Wu; Wenjun Chen (NeuroMolecular Medicine, 2025)

3D printing of scaffolds for articular cartilage/osteochondral regeneration: Design, performance, and applications - Luhao Li; Guang Shi; Zijian Wu; Zhenxin Cai; Junwu Wang; Zhuowen Hao; Renxin Chen; Zhenzhou Piao; Chao Chen; Jingfeng Li (Chemical Engineering Journal, 2025)

Unveiling uncertainties in soil organic carbon modeling: the critical role of climate response functions - Huiwen Li; Yue Cao; Jingfeng Xiao; Wenxin Zhang; Yiping Wu; Arshad Ali; Zuoqiang Yuan (Environmental Modelling & Software, 2025)

Effects of combined stressors to TCDD and high temperature on HSP/CYPs signaling in the zebrafish embryos/larvae - Hongsong Chen; Hao Chen; Lian Hua; Yunqi Gao; Yuehua Yao; Yangfan Xu; Jingfeng Yang; Lingtian Xie; Yongju Luo; Ting Huang; Hongxing Chen; Xuguang Lin; et al. (Environmental Pollution, 2025)

Integrated Proteomics and Metabolomics Analyses Reveal Molecular Mechanism of Cardiac Resynchronization Therapy Against Cardiac Fibrosis and Ventricular Arrhythmias - Maoxiong Wu; Haiying Li; Jing Tan; Jingting Mai; Shaoxin Zheng; Qiong Qiu; Bingqing Deng; Hanlu Lv; Peiwei Wang; Jingfeng Wang; Yangxin Chen; Woliang Yuan (Cardiovascular Toxicology, 2025)

Fluoride removal from coal mining water using novel polymeric aluminum modified activated carbon prepared through mechanochemical process - Yixiang Bao; Yonghui Qi; Qiao Li; Lei Wang; Zhiguo Cao; Jie Li; Min Wu; Jun Chen; Haiqin Zhang; Qiang Guo; Binbin Jiang; Jinkui Zhong; et al. (Journal of Environmental Sciences, 2024)

Elimination of representative antibiotic-resistant bacteria, antibiotic resistance genes and ciprofloxacin from water via photoactivation of periodate using FeS2 - Fuyang Liu; Yutao Shen; Yanghui Hou; Jingfeng Wu; Yong Ting; Chenyi Nie; Meiping Tong (Journal of Hazardous Materials, 2024)

Phenacetin promoted the rapid start-up and stable maintenance of partial nitrification: Responses of nitrifiers and antibiotic resistance genes - Yi Zhang; Zejie Wu; Yongqing Gao; Jingfeng Gao; Fangbo Bao; Yifan Zhao; Yi Guo; Ying Liu (Science of The Total Environment, 2024)

The synergistic effect of periodate/ferrate (VI) system on disinfection of antibiotic resistant bacteria and removal of antibiotic resistant genes: The dominance of Fe (IV)/Fe (V) - Hao Chen; Jingfeng Gao; Qian Wang; Ying Liu; Lei Wu; Xiaoyu Fu; Yi Guo; Hanyi Wang; Yuxuan Wang (Journal of Hazardous Materials, 2024)

Establishing the global isoscape of leaf carbon in C3 plants through the integrations of remote sensing, carbon, geographic, and physiological information - Xiang Wang; Guo Chen; Joseph Awange; Yongze Song; Qi Wu; Xiaowei Li; Edmund February; Gustavo Saiz; Ralf Kiese; Xing Li; Jingfeng Xiao; Xiaoxiang Zhao; et al. (Remote Sensing of Environment, 2024)

Impact of the Three Gorges Dam on hydrological connectivity and vegetation growth of Poyang Lake floodplain, China - Jinfeng Zeng; Jingfeng Qiu; Zeyu Wu; Xinggen Liu; Yunliang Li (Journal of Hydrology, 2024)

Remote sensing image cloud detection using a shallow convolutional neural network - Dengfeng Chai; Jingfeng Huang; Minghui Wu; Xiaoping Yang; Ruisheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Aflatoxin B1-induced early developmental hepatotoxicity in larvae zebrafish - Chi Feng; Hongxia Bai; Xu Chang; Zhixuan Wu; Wu Dong; Qianqian Ma; Jingfeng Yang (Chemosphere, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Work along both lines: The p-chloro-m-cresol achieved stable and long-term partial nitrification and inhibited the enrichment of resistance genes - Yi Guo; Jingfeng Gao; Zejie Wu; Ziqiao Li; Yi Zhang; Haoran Zhang (Chemical Engineering Journal, 2023)

The spread of different resistance genes fractions in nitrification system under chronic exposure to varying alkyl chain length benzalkyl dimethylammonium compounds - Haoran Zhang; Jingfeng Gao; Mingyan Zhao; Zhiqi Wang; Dingchang Li; Zejie Wu; Yi Zhang; Ying Liu (Bioresource Technology, 2023)

Magnetically responsive nanoplatform targeting circRNA circ_0058051 inhibits hepatocellular carcinoma progression - Song You; Zijin Luo; Niangmei Cheng; Ming Wu; Yongping Lai; Fei Wang; Xiaoyuan Zheng; Yingchao Wang; Xiaolong Liu; Jingfeng Liu; Bixing Zhao (Drug Delivery and Translational Research, 2023)
Circular RNAs (circRNAs) are a class of highly stable and closed-loop noncoding RNA that are involved in the occurrence and development of hepatocellular carcinoma (HCC). However, little is known about the therapeutic role of circRNAs in HCC. We found that high circ_0058051 expression was negatively correlated with the prognosis of HCC patients. Circ_0058051 knockdown attenuated the proliferation and colony formation, meanwhile inhibited migration of HCC cells. Circ_0058051 may be used as a target for HCC gene therapy. We synthesized a novel small interfering RNA (siRNA) delivery system, PEG-PCL-PEI-C14-SPIONs (PPPCSs), based on superparamagnetic iron oxide nanoparticles (SPIONs). PPPCSs protected the siRNA of circ_0058051 from degradation in serum and effectively delivered siRNA into SMMC-7721 cells. Meanwhile, intravenous injection of the PPPCSs/siRNA complex could inhibit tumor growth in the subcutaneous tumor model. In addition, the nanocomposite is not toxic to the organs of nude mice. The above results show that PPPCSs/si-circ_0058051 complex may provide a novel and promising method of HCC treatment. Graphical abstract

Inhibition of Nitrospira and Nitrotoga by paracetamol achieved the rapid start-up and long-term stable operation of partial nitrification for low-strength ammonium wastewater - Yingchao Cui; Jingfeng Gao; Zejie Wu; Zhiqi Wang; Yifan Zhao; Yi Guo (Chemical Engineering Journal, 2023)

Different acesulfame potassium fate and antibiotic resistance propagation pattern in nitrifying and denitrifying sludge systems - Ziqiao Li; Jingfeng Gao; Yifan Zhao; Zhiqi Wang; Yingchao Cui; Dingchang Li; Yi Guo; Zejie Wu; Liqin Zeng (Science of The Total Environment, 2023)

Short-term stress of quaternary ammonium compounds on intracellular and extracellular resistance genes in denitrification systems - Mingyan Zhao; Jingfeng Gao; Ying Liu; Zhiqi Wang; Zejie Wu; Haoran Zhang; Yi Zhang (Chemical Engineering Journal, 2023)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Decipher soil organic carbon dynamics and driving forces across China using machine learning - Huiwen Li; Yiping Wu; Shuguang Liu; Jingfeng Xiao; Wenzhi Zhao; Ji Chen; Georgii Alexandrov; Yue Cao (Global Change Biology, 2022)
The dynamics of soil organic carbon (SOC) play a critical role in modulating global warming. However, the long‐term spatiotemporal changes of SOC at large scale, and the impacts of driving forces remain unclear. In this study, we investigated the dynamics of SOC in different soil layers across China through the1980s to 2010s using a machine learning approach and quantified the impacts of the key factors based on factorial simulation experiments.Our results showed that the latest (2000–2014) SOC stock in the first meter soil (SOC 100 ) was 80.68 ± 3.49 Pg C, of which 42.6% was stored in the top 20 cm, sequestrating carbon with a rate of 30.80 ± 12.37 g C m −2 yr −1 since the 1980s. Our experiments focusing on the recent two periods (2000s and 2010s) revealed that climate change exerted the largest relative contributions to SOC dynamics in both layers and warming or drying can result in SOC loss. However, the influence of climate change weakened with soil depth, while the opposite for vegetation growth. Relationships between SOC and forest canopy height further confirmed this strengthened impact of vegetation with soil depth and highlighted the carbon sink function of deep soil in mature forest. Moreover, our estimates suggested that SOC dynamics in 71% of topsoil were controlled by climate change and its coupled influence with environmental variation (CE). Meanwhile, CE and the combined influence of climate change and vegetation growth dominated the SOC dynamics in 82.05% of the first meter soil. Additionally, the national cropland topsoil organic carbon increased with a rate of 23.6 ± 7.6 g C m −2 yr −1 since the 1980s, and the widely applied nitrogenous fertilizer was a key stimulus. Overall, our study extended the knowledge about the dynamics of SOC and deepened our understanding about the impacts of the primary factors.

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Estimating biophysical parameters of rice with remote sensing data using support vector machines - XiaoHua Yang; JingFeng Huang; YaoPing Wu; JianWen Wang; Pei Wang; XiaoMing Wang; Alfredo R. Huete (Science China Life Sciences, 2011)